A multi scale multi domain model for large format lithium-ion batteries. (10th October 2021) - Schmidt, Adrian; Oehler, Dieter; Weber, André; Wetzel, Thomas; Ivers-Tiffée, Ellen
Highlights: A multi scale multi domain model for large sized lithium-ion battery cells. Homogenization of electrode and distinct material layers. Consideration of inhomogeneous temperature and locally fluctuating cell conditions. Parametrization and simulation of a 120 Ah LIB large format cell. Comparison of four different cooling concepts. Abstract: A multi scale multi domain (MSMD) model for large format lithium-ion battery (LIB) cells is presented. In our approach the homogenization is performed on two scales (i) from the particulate electrodes to homogenized electrode materials using an extended Newman model and (ii) from individual cell layer materials to a homogenized battery material with anisotropic electrical and thermal transport properties. Both intertwined homogenizations are necessary for considering electrochemical-thermal details related to microstructural and material features of electrode and electrolyte layers at affordable computational costs. Simulation results validate the MSMD model compared to the homogenized Newman model for isothermal cases. The strength of the MSMD model is demonstrated for non-isothermal conditions, namely for a 120 Ah cell discharged with four different cooling concepts: (i) without cooling (ii) with a base plate cooling (iii) with a tab cooling and (iv) with a side cooling. As one result, temperature gradients cause a local peak discharge up to 2.8 C for a global 2 C discharge rate. Graphical abstract: Image, graphical abstract